TRANSFORMASI KARAKTER KONFLIK ASIMETRIS DAN RELEVANSINYA TERHADAP ADAPTASI HUKUM HUMANITER DI LINGKUP OPERASI MILITER MODERN - Andri Hadiyanto; Gusti Sopyannur, Tarsius Susilo, Zulkifli, Wahyu Tunggul Wiratama (JOURNAL OF LAW AND NATION, 2025)
The transformation of global conflict patterns reflects a profound departure from conventional warfare toward asymmetrical combat models. This paradigm shift is characterized by the active role of non-state actors, guerrilla-style tactics, the strategic use of civilian spaces as battlegrounds, and the absence of traditional frontlines, thereby generating substantial challenges to the applicability and effectiveness of International Humanitarian Law (IHL). Within the scope of modern military operations, such a landscape necessitates normative adaptation of core IHL principles, including distinction, proportionality, and military necessity. This paper seeks to critically examine how the evolving dynamics of asymmetric warfare impact the operationalization of humanitarian law and assess the extent to which these legal principles remain resilient amid the realities of blurred combatant status, covert hostilities, and the deliberate use of civilian populations as shields. Using a qualitative-analytical methodology through literature review, international legal instruments, and empirical case studies, this article emphasizes the imperative of recontextualizing the legal framework to better address the spectrum of contemporary threats. The findings advocate for conceptual refinement and the harmonization of military doctrine with international legal standards to ensure both legitimacy and humanitarian protection in complex modern battlefields.